Pemanfaatan Plant Growth Promoting Rhizobacteria Guna Mendukung Pertanian di Kecamatan Jelbuk, Kabupaten Jember - Maria Azizah; Fadil Rohman; Suwardi Suwardi; Rahmat Ali Syaban; Edi Siswadi; M. Zayin Sukri; Refa Firgiyanto; Gallyndra Fatkhu Dinata; Tri Rini Kusparwanti; Dian Hartatie (Journal of Community Development, 2023)
Jelbuk District, Jember Regency is an area with natural resource potential in the form of superior agricultural commodities which include food crops, horticulture and plantations such as rice, corn, cayenne pepper, bananas, coconut and tobacco. This potential makes Jelbuk District one of the areas that makes an important contribution in producing agricultural products in Jember Regency. However, the sustainability of the potential of natural resources and the contribution of agriculture in Jelbuk District has faced the problem of local farmers who were still dependent on chemical fertilizers and pesticides which besides being expensive can also be detrimental to the environment. In order to solve these problems, it was necessary to carry out socialization and counseling activities related to the utilization of plant growth promoting rhizobacteria (PGPR) which have been widely studied to increase plant growth and production as well as the efficiency of the use of chemical inputs. Community service activities were conducted in August 2022 in Sucopangepok Village, Jelbuk District, Jember Regency through three stages, namely situation analysis and preparation, socialization and counseling and assistance. Socialization and counseling is carried out with material assistance using the panel method. The results of community service show that science and technology transfers related to the use of PGPR in plant cultivation can be accepted by partners as shown by the high enthusiasm of partners through active discussions on programs that have been socialized.